Hospital image and service quality on patient satisfaction and patient loyalty of Mojowarno Christian hospital - Felix Setiawan Budi; Pauline Henriette Pattyranie Tan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Patient loyalty is an essential factor contributing to increased in-patient hospital visits. This study aims to understand the importance of patient loyalty in the context of increasing patient visits. This study examines the impact of service quality variables, hospital brand image, patient-perceived value, and patient satisfaction on patient loyalty. Indonesia Mojowarno Christian Hospital located in the peripheral area of ​​Jombang city, covering a wide health area. Looking at the data on hospital visits, there is still a high potential for an increase in the number of visits. Due to the unknown and uncertain population size, it is limited to patients at the Mojowarno Jombang Christian Hospital. The sampling technique is purposive sampling. The minimum number of samples used is 160 samples. The analysis used was PLS-SEM analysis. This research model can adequately predict patient satisfaction variables as mediation, so this research model can be recommended to be replicated and tested in different populations. From the results of the structural model analysis, Hospital Image is not proven to have an influence neither Patient Satisfaction nor Patient Loyalty, Service Quality affect both Patient Satisfaction and Patient Loyalty, and Patient Satisfaction has influence on Patient Loyalty.